2014
DOI: 10.1111/coep.12098
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom and State Bond Ratings

Abstract: Are state bond ratings, ceteris paribus, related to economic freedom? We test for the relationship between economic freedom and an aggregate index comprised of ratings by Standard & Poor, Moody's, and Fitch. We also test for a relationship between economic freedom and the ratings by these three agencies individually. With a sample covering all 50 states for the period 1995-2008, the evidence strongly indicates that state bond ratings are positively and significantly related to overall economic freedom as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Heller and Stephenson (2014) used the index to measure economic freedom and its role in the determination of states' unemployment, labor-force participation, and employmentpopulation rates. Belasen, Hafer, and Jategaonkar (2015) found that EFNA scores were significantly related to state bond ratings. Finally, the results contained within Wiseman and Young (2013) provide a suggestion that EFNA scores are correlated with entrepreneurial activity and that economic freedom might be impacting state income levels through changes in entrepreneurial activity.…”
Section: B State Business Climate Measuresmentioning
confidence: 93%
“…Heller and Stephenson (2014) used the index to measure economic freedom and its role in the determination of states' unemployment, labor-force participation, and employmentpopulation rates. Belasen, Hafer, and Jategaonkar (2015) found that EFNA scores were significantly related to state bond ratings. Finally, the results contained within Wiseman and Young (2013) provide a suggestion that EFNA scores are correlated with entrepreneurial activity and that economic freedom might be impacting state income levels through changes in entrepreneurial activity.…”
Section: B State Business Climate Measuresmentioning
confidence: 93%
“…are political stability or corruption control as measures which similar to freedom index (Kalloub et al, 2018). Researcher may also use other dependent variables, such as state bond ratings (Belasen et al, 2015;Calcagno & Benefield, 2013) or spread between state bonds and risk free bonds (Pačebutaitė, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these considerations also drive home the importance of an independent judiciary. Poterba and Rueben 1999) and economic freedom (Belasen, Hafer, and Jategaonkar 2015;Calcagno and Benefield 2013). This final strand of the literature looks at a number of institutional factors that appear to influence state bond ratings, including anti-deficit and anti-spending measures, tax and expenditure limits, and debt referenda.…”
Section: Applications For Practicementioning
confidence: 99%
“…In order to operationalize these three measures in a manner suitable for empirical investigation the paper follows a procedure developed by Depken and Lafountain (2006) and implemented by Belasen et al (2015); Calcagno and Benefield (2013); and Schelker (2012). Under this procedure each state's bond rating is converted into a numerical value, where the value for state i in year t provided by rating service k is R itk ef1; .…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
See 1 more Smart Citation